"I have never talked to anyone to free my mind" - challenges surrounding status disclosure to adolescents contribute to their disengagement from HIV care: a qualitative study in western Kenya - Judith J. Toromo; Edith Apondi; Winstone M. Nyandiko; Mark Omollo; Salim Bakari; Josephine Aluoch; Rami Kantor; J. Dennis Fortenberry; Kara Wools-Kaloustian; Batya Elul; Rachel C. Vreeman; Leslie A. Enane (BMC, 2022)
Abstract Introduction Adolescents living with HIV (ALHIV, ages 10-19) experience complex barriers to care engagement. Challenges surrounding HIV status disclosure or non-disclosure to adolescents may contribute to adolescent disengagement from HIV care or non-adherence to ART. We performed a qualitative study to investigate the contribution of disclosure challenges to adolescent disengagement from HIV care. Methods This was a qualitative study performed with disengaged ALHIV and their caregivers, and with healthcare workers (HCW) in the Academic Model Providing Access to Healthcare (AMPATH) program in western Kenya. Inclusion criteria for ALHIV were ≥1 visit within the 18 months prior to data collection at one of two clinical sites and nonattendance ≥60 days following their last scheduled appointment. HCW were recruited from 10 clinics. Analysis was conducted by multiple independent coders, and narratives of disclosure and care disengagement were closely interrogated. Overarching themes were elucidated and summarized. Results Interviews were conducted with 42 disengaged ALHIV, 32 caregivers, and 28 HCW. ALHIV were average age 17.0 (range 12.9-20.9), and 95% indicated awareness of their HIV diagnosis. Issues surrounding disclosure to ALHIV presented important barriers to HIV care engagement. Themes centered on delays in HIV status disclosure; hesitancy and reluctance among caregivers to disclose; struggles for adolescents to cope with feelings of having been deceived prior to full disclosure; pervasive HIV stigma internalized in school and community settings prior to disclosure; and inadequate and unstructured support after disclosure, including for adolescent mental health burdens and for adolescent-caregiver relationships and communication. Both HCW and caregivers described feeling inadequately prepared to optimally handle disclosure and to manage challenges that may arise after disclosure. Conclusions Complex challenges surrounding HIV status disclosure to adolescents contribute to care disengagement. There is need to enhance training and resources for HCW, and to empower caregivers to support children and adolescents before, during, and after HIV status disclosure. This should include counseling caregivers on how to provide children with developmentally-appropriate and accurate information about their health from an early age, and to support adolescent-caregiver communication and relationships. Optimally integrating peer support can further promote ALHIV wellbeing and retention in care.